2000
DOI: 10.1074/jbc.m006801200
|View full text |Cite
|
Sign up to set email alerts
|

The Core Histone N Termini Function Independently of Linker Histones during Chromatin Condensation

Abstract: The relationships between the core histone N termini and linker histones during chromatin assembly and saltdependent chromatin condensation were investigated using defined chromatin model systems reconstituted from tandemly repeated 5 S rDNA, histone H5, and either native "intact" core histone octamers or "tailless" histone octamers lacking their N-terminal domains. Nuclease digestion and sedimentation studies indicate that H5 binding and the resulting constraint of entering and exiting nucleosomal DNA occur t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 66 publications
(91 reference statements)
2
83
0
Order By: Relevance
“…The production of very homogeneous and tightly folded 30-nm chromatin fibers from long nucleosome arrays with different nucleosome repeat lengths has permitted us to obtain accurate measurements of fiber dimensions and hence nucleosome packing ratios. Importantly, unlike previous chromatin reconstitution experiments (35,38,44), our nucleosome arrays contain a native-like complement of linker histone (11), which is critical for obtaining correct folding and maximal compaction (15,32,45). We find that over the range of nucleosome repeat lengths analyzed, there are two discrete classes of fiber structure, one 33 nm in diameter and with Ϸ11 nucleosomes per 11 nm, and the other Ϸ44 nm in diameter and with Ϸ15 nucleosomes per 11 nm.…”
Section: Discussion Chromatin Fibers Form Two Discrete Structural Clamentioning
confidence: 77%
“…The production of very homogeneous and tightly folded 30-nm chromatin fibers from long nucleosome arrays with different nucleosome repeat lengths has permitted us to obtain accurate measurements of fiber dimensions and hence nucleosome packing ratios. Importantly, unlike previous chromatin reconstitution experiments (35,38,44), our nucleosome arrays contain a native-like complement of linker histone (11), which is critical for obtaining correct folding and maximal compaction (15,32,45). We find that over the range of nucleosome repeat lengths analyzed, there are two discrete classes of fiber structure, one 33 nm in diameter and with Ϸ11 nucleosomes per 11 nm, and the other Ϸ44 nm in diameter and with Ϸ15 nucleosomes per 11 nm.…”
Section: Discussion Chromatin Fibers Form Two Discrete Structural Clamentioning
confidence: 77%
“…This result indicates that Sir3p binding to nucleosomal substrates and naked DNA was not DNA sequence-dependent. Importantly, rSir3p-dependent assembly of supershifted species also occurred in 50-150 mM NaCl and 2 mM MgCl 2 (data not shown), demonstrating that Sir3p can bind to nucleosomal arrays under ionic conditions where the arrays are extensively folded (24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 93%
“…The 12-mer nucleosomal arrays (208-12 NA) used in these experiments were obtained by reconstituting chicken erythrocyte histone octamers onto a DNA template (208-12 DNA) consisting of 12 tandem repeats of 208-1 DNA (23). The intrinsic structural dynamics of 208-12 NA have been characterized extensively both in the absence (24,25) and presence (26,27) of linker histones, providing a firm foundation for interpreting the effects of Sir3p binding on higher order chromatin structure. Incubation of Sir3p with 208-12 NA at r Sir3p ϭ 0.1-25 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that higher-order folding of nucleosomal arrays is dependent on the core histone Ntermini rather than on linker histones (17)(18)(19)(20)(21). Chromatin condensation has been observed in vitro in the absence of linker histones (22), and it has been hypothesized that linker histone binding does not direct the formation of folded chromatin structure (23,24). Linker histone knockout experiments carried out in the protozoan Tetrahymena showed that histone H1 is not essential for nuclear assembly and cell survival, but it seems to be involved in the regulation of specific gene expression (25)(26)(27).…”
mentioning
confidence: 99%